Seen Safety Performance from the Perspective of Safety Plan, Safety Behavior, and Safety Culture through Management Control as a Moderating Variable: A Conceptual Framework - Jarman Setiadi; Dudi Permana; Setyo Riyanto (Budapest International Research and Critics University, 2022)
This research aims seen safety performance from the perspective of safety plan, safety behavior, and safety culture through management control as a moderating variable, a conceptual framework. The research method used is a qualitative analysis method from the perspective of the conceptual framework. Based on the results of the literature review obtained in this study, there is a paradigm that is developing today that it seems as if work safety is only for the protection of labor safety alone, while the occupational safety factor is also very much needed by companies to maintain investment sustainability.